Amplifying Purchase Decisions: The Impact of Social Media Marketing, e-WOM, and Celebrity Endorsements - Putra, Yoan Ananda; Budiman, Andika Nuraga (Marketing and Business Strategy, 2024)
This study aims to examine the influence of social media marketing and electronic word of mouth on purchase decisions and celebrity endorsers as moderation. The population in this study were Kopi Lain Hati customers in Cempaka Putih. Sampling was carried out using the questionnaire method, and the number of samples was 110 respondents. The type of data used is quantitative data. In collecting data, this study used a questionnaire. The results of this study indicate that Social Media Marketing and Electronic Word of Mouth have a positive and significant effect on Purchase Decisions. Then Celebrity Endorsers are not able to moderate Social Media Marketing on Purchase Decisions. At the same time, Celebrity Endorsers are able to moderate Electronic Word of Mouth but are debilitating on Purchase Decisions. Managerial Implications This research offers important insights for marketing managers and business owners regarding the importance of social media marketing strategies and the use of electronic word of mouth (e-WOM) in influencing consumer purchasing decisions. This study offers novelty by analyzing the influence of social media marketing, electronic word of mouth, and the use of celebrity endorsers on purchasing decisions in the context of a local coffee business, namely Kopi Lain Hati.